Introdução ao aspecto verbal do grego antigo - Sant'Anna, Jean Paul Campos e [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This dissertation focuses on the category of aspect in Ancient Greek. Aspects is typically a semantic and morphological characteristic of verbs in the languages where it occurs, as in Ancient Greek. Semantically it is related to how time is considered in the discourse. It shows how events are specified in relation to time in sentences. From the morphological point of view, aspect is as morphological morpheme aggregated to certain verbal forms such as present, perfect, aorist and future. The dissertation presents the morphological structure of Ancient Greek verbs, to show how the aspectual meaning is associated to morphemes. In relation to the literature, the notion of aspect is presented in grammars and in specific works by linguists. A review of the principal ideas is presented and discussed. It is assumed that the aspectual meaning in verbs is a morphological mark, but it also depends on the meaning conveyed by the lexemes. New works on the subject brought new insights not only on the definition of aspect, but also in the analysis of its occurrence in languages, including a review of the traditional interpretation of aspect in Ancient Greek. This dissertation detected some remaining problems and it brings possible solutions. In this way, this dissertation states that in Ancient Greek verbs the elements that define the aspectual meaning are morphologically determined by special verbal morphemes, but it is also important to take into account the semantic meaning of the lexemes. Only when both elements are considered, it is possible to assign the aspectual meaning to a sentence

Essa dissertação tem como objetivo a categoria aspect no Grego Antigo. Aspecto é tipicamente uma característica semântica e morfológica dos verbos das línguas naturais onde ocorre, como em Grego Antigo. Semanticamente mostra como eventos são especificados em relação ao tempo nas sentenças. Do ponto de vista morfológico, aspecto é um morfema adicionado a certas formas verbais como o presente, perfeito, o aoristo e o futuro. Esta dissertação apresenta a estrutura morfológica dos verbos do Grego Antigo, a fim de mostrar como o valor aspectual é associado aos morfemas. Em relação à literatura, a noção de aspecto está presente em gramáticas e em trabalhos específicos de linguistas. Uma revisão das principais idéias é apresentada e discutida. Assumi-se que o valor aspectual nos verbos é uma marca morfológica que depende dos valores expressos pelo lexema verbal. Novos trabalhos sobre este tema trazem novas visões não só sobre a definição de aspecto, como também sobre análises de sua ocorrências nas línguas naturais, incluindo uma revisão sobre a tradicional interpretação do aspecto em Grego Antigo. Esta dissertação detecta alguns problemas remanescentes e traz possíveis soluções para eles. Desta forma, esta dissertação afirma que nos verbos do Grego Antigo os elementos que definem o valor aspectual são morfologicamente determinados por morfemas verbais especiais, mas deve-se levar em conta o as classes aspectuais que se enquadram os lexemas verbais em questão. Somente quando ambos os elementos são considerados, é possível atribuir o valor aspectual de uma sentença
Keywords: Linguística; Semântica; Lingua grega; Linguistics